الأساليب الإنشائية في الأربعين النووية - Muammar (Program Studi Pendidikan Bahasa Arab (PBA), Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Instutut Agama Islam Negeri (IAIN) Palu, 2020)
This study aims to describe the secrets contained in the words of the Prophet Muhammad peace be upon him, especially in terms of structuralism in the choice of words spoken from his oral Muhammad peace be upon him, because everything that is spoken from the oral of the Prophet Muhammad is a revelation that is absolute to believe, then in terms of fluency this is a treasure in the branch of balaghah science. This study used a qualitative method with descriptive analysis, where this method focuses on the words of the Prophet Muhammad that written in the Al 'Arbai'in An Nawaiyah book, and also the structural techniques that researched in this study only focuses on a few form of words that is al amr (command word), an nahyu (prohibition word), al istifham (question word), an nidaa (call word). The findings of this study are the words os the Prophet Muhammad that written on Al 'Arbai'in An Nawaiyah book contain many forms of structural techniques with their respective objectives and purposes, one example is the word (يَا مُحَمَّدُ) in hadith number 2 is included in the category of an nidaa (calling words), which in balaghah science functions to call someone who is some distance away drom the speaker, and also another function is a call of honor to someone who has a higher rank than the speaker.